Urbanization and Urban Services Policy in Latin America (Andamios, Revista de Investigación Social, 2013)
This article reflects on urban infrastructure services in Latin America. It analyzes this services as goods produced and distributed collectively, that support the operation (and reproduction) of the urban agglomeration. This paper tries to study the services as part of process of urbanization inside the structural determinations and the particular processes (social and political) that define them. It develops a brief conceptualization of urban services in capitalist urbanization in general and in Latin America, introducing the issue of guidance, in two phases of capitalism, Keynesianism, welfare and neoliberal restructuring.
Keywords: Latin-American Urbanization; Urban Services; Urban Infrastructure; Orientation; Decommodification